If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + 5 = 4a + 10 Reorder the terms: 5 + 7a = 4a + 10 Reorder the terms: 5 + 7a = 10 + 4a Solving 5 + 7a = 10 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 5 + 7a + -4a = 10 + 4a + -4a Combine like terms: 7a + -4a = 3a 5 + 3a = 10 + 4a + -4a Combine like terms: 4a + -4a = 0 5 + 3a = 10 + 0 5 + 3a = 10 Add '-5' to each side of the equation. 5 + -5 + 3a = 10 + -5 Combine like terms: 5 + -5 = 0 0 + 3a = 10 + -5 3a = 10 + -5 Combine like terms: 10 + -5 = 5 3a = 5 Divide each side by '3'. a = 1.666666667 Simplifying a = 1.666666667
| -6(1-8k)+K=239 | | 8x-18-x-9= | | 7x+10=157 | | 7a+5=4 | | X/5-10=1 | | X/3=14/12 | | f(-2)=3x^2-5x+2 | | (5+37)+63=5+(37+63) | | 4n-7=9+7 | | 3(90-x)=180-x/3 | | 0=-0.1x^2+23x-1700 | | -16=4(x-3) | | (-3.4)-5/4 | | 6(4s+9)=294 | | 2y+5=6y+7 | | Y=1.5x-2.6 | | 15+6x=45x+8 | | 169+(x*x)=268.96 | | 8x+5=9x+9 | | -81=-3(-4x+5) | | 29-3m=-(m-8)+5 | | f(3)=3x^2-5x+2 | | c(c)-4c=0 | | 15(x-5)=-15 | | -2x+4x+6=26 | | p^2=-86-18p | | q=2-0 | | 6x-13-15=0 | | 2(3n-5)=(2n+5)+7 | | (u-3)*8=40 | | y=(-4)-2 | | (q-4)*4=32 |